Simulated diagnostic cerebral angiography in neurosurgical training: a pilot program. (10th May 2012) - Spiotta, Alejandro M; Rasmussen, Peter A; Masaryk, Thomas J; Benzel, Edward C; Schlenk, Richard
Abstract : Introduction: Surgical simulation provides a zero-risk setting in which technical skills can be obtained through repetition. The feasibility and utility of simulated diagnostic cerebral angiography among neurosurgical residents and fellows was studied using an endovascular biplane angiography simulator. Methods: Ten neurosurgical residents and four endovascular neurosurgery fellows were recruited into a standardized training protocol consisting of a didactic, demonstration and hands-on learning environment using the Simbionix simulator. Participants were instructed to catheterize the right internal carotid artery, left internal carotid artery and left vertebral artery. The task was repeated five times. Results: All participants demonstrated improvement over the five trials. Residents performed actions that were perceived as potentially dangerous (n=8) while fellows performed the procedure with superior technique. Residents performed the task with an initial total procedure and fluoroscopy time of 6.6±4.3 min and 4.9±3.7 min, respectively, and improved on the fifth trial to 3.4±1.3 min (p=0.03) and 2.3±0.78 min (p=0.004), respectively. Residents approximated the efficiency of fellows for the third and fourth trial. Conclusions: Incorporating an endovascular simulator is feasible for training purposes in a neurosurgical residency program. This study provides objective documentation of the facilitation of technical angiography skill acquisition by the use of simulation technology.